Applications of the Covariant Spectator Theory - Stadler, Alfred (2012)
In this talk I provide a short overview of applications of the so-called Covariant Spectator Theory to two- and three-nucleon systems. It is a quasi-potential formalism based on relativistic quantum field theory, and can be derived from a reorganization of the complete Bethe-Salpeter series. In this framework, we con- structed two one-boson-exchange models, called WJC-1 and WJC-2, for the neutron-proton interaction that fit the 2007 world data base, containing several thousands of neutron-proton scattering data below 350 MeV, with a χ2/Ndata close to 1. The close fit to the observables implies that the phase shifts derived from these models can be interpreted as new phase-shift analyses, which can be used also in nonrelativistic frameworks. Both models have a considerably smaller number of adjustable parameters than are present in realistic nonrel- ativistic potentials, which shows that the inclusion of relativity actually helps to achieve a realistic description of the interaction between nucleons. This became also evident in calculations of the three-nucleon bound state, where the correct binding energy is obtained without additional irreducible three-body forces which are needed in nonrelativistic calculations. In addition, calculations of the electromagnetic form factors of helium- 3 and of the triton in complete impulse approximation also give very reasonable results, demonstrating the Covariant Spectator Theory’s ability to describe the structure of the three-nucleon bound states realistically.